Optimization of Energy for Proton Therapy with Pencil Beam Collimator Model in Craniopharyngioma Tumor Using MCNP6 Code - Putri, Weni Antari; Riyatun, Riyatun; Darmanto, Darmanto; Suharyana, Suharyana; Arianto, Fajar (Journal of Physics and Its Applications, 2023)
Computational simulations of proton therapy with a pencil beam collimator for craniopharyngioma have been done using MCNP6. A pencil beam was radiated towards cube shaped tumor cells in size 1.2 cm, located at a 5.4 cm depth from the surface of the scalp. A 0.1 cm pencil beam was radiated from the left 19.6 cm from the scalp. The cube of tumor cell is divided into the front layer, middle layer, and back layer. Each layer of the tumor cell is divided into 9 cubicles, thus there are 27 cubicles. Using various energy from 108 MeV to 115 MeV and various intensity of energy for each irradiation, it produces the dose for each cubicle in unit MeV/gram per proton. The best isodoses occurred in 5 variations of energy which is 108.2; 111.2; 113.4; 114.7 and 115 MeV. The healthy organ that received the largest dose of the proton is the brain, it is (7.38±0.01)×10-2 MeV/gram per proton, or only 0.412% compared to the tumor cell dose.